Health Risk Exposure Assessment of Migration of Perfluorooctane Sulfonate and Perfluorooctanoic Acid from Paper and Cardboard in Contact with Food under Temperature Variations - Shu-Han You; Chun-Chieh Yu (Foods, 2023)
Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) are extensively used in food-contact paper and cardboard. However, they may migrate from food-contact materials to food, and the migration rate may be increased at elevated temperatures. In addition, there is a positive association of PFOS/PFOA levels with total cholesterol. Therefore, this study aims to assess the human health risk of increased total cholesterol associated with long-term exposure to PFOS and PFOA migration from food-contact paper and cardboard under temperature variation scenarios in adults. An exposure assessment was performed using an uptake dose model to estimate the uptake doses of PFOS and PFOA for the high-, intermediate-, and low-exposure scenarios. Benchmark dose (BMD) modeling was conducted to describe the dose–response relationships between PFOS/PFOA and total cholesterol levels. Finally, a margin of exposure (MOE) approach was used to characterize the risk. The results of the exposure assessment showed that PFOS and PFOA uptake doses in the high-exposure scenarios were around one and two orders of magnitude greater than those in the intermediate- and low-exposure scenarios, respectively. Under high-exposure scenarios, the uptake levels of hundredth-percentile PFOS and PFOA at high temperatures may raise health concerns (MOE < 1). This study provides a methodology to assess the health risks associated with exposure to migration of food contaminants from various types of paper and cardboard that come into contact with food.